2018
DOI: 10.1021/acsami.8b06101
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Aligned N-Doped Diamond/Graphite Hybrid Nanosheets Epitaxially Grown on B-Doped Diamond Films as Electrocatalysts for Oxygen Reduction Reaction in an Alkaline Medium

Abstract: Diamond/graphite hybrid nanosheets (DGNSs) have been epitaxially grown on boron-doped diamond (BDD) films from CH/H mixture gas by microwave plasma chemical vapor deposition. The DGNSs are vertically aligned on the crystal facets of the BDD films uniformly, densely, and orderly. The DGNSs are composed of the core diamond sheets and the surface graphitic overlayers, which possess an open edge structure. By posttreatment in NH atmosphere in a microwave plasma or a tube furnace, the N-doped DGNSs (NDGNSs) were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
0
12
0
1
Order By: Relevance
“…Pengendapan uap polimer dan substrat Pengendapan uap polimer telah membuka pintu ke berbagai bahan yang akan sulit, dan dalam beberapa kasus dan tidak mungkin, untuk diproduksi dengan cara lain. Sebagai contoh, banyak polimer yang bermanfaat, seperti bahan penumpahan air untuk melindungi komponen industri atau implan biologis, dibuat dari prekursor yang tidak dapat larut, sehingga tidak dapat diproduksi menggunakan metode berbasis solusi konvensional (90)(91)(92)(93). Pekerjaan Gleason pada CVD berbasis polimer dimulai pada 1990-an, ketika dia melakukan eksperimen dengan Teflon, senyawa klorin dan fluor.…”
Section: A Proses Chemical Vapor Deposisiunclassified
“…Pengendapan uap polimer dan substrat Pengendapan uap polimer telah membuka pintu ke berbagai bahan yang akan sulit, dan dalam beberapa kasus dan tidak mungkin, untuk diproduksi dengan cara lain. Sebagai contoh, banyak polimer yang bermanfaat, seperti bahan penumpahan air untuk melindungi komponen industri atau implan biologis, dibuat dari prekursor yang tidak dapat larut, sehingga tidak dapat diproduksi menggunakan metode berbasis solusi konvensional (90)(91)(92)(93). Pekerjaan Gleason pada CVD berbasis polimer dimulai pada 1990-an, ketika dia melakukan eksperimen dengan Teflon, senyawa klorin dan fluor.…”
Section: A Proses Chemical Vapor Deposisiunclassified
“…1,9 Conventionally, Pt and its alloys have been proven to be the most efficient, and thus most widely used, electrocatalysts for the ORR, as a result of their high catalytic. 6,10 However, as well as improving the ORR activity, studies have been focused on lowering the Pt content of electrocatalysts to reduce costs. This can be achieved using another substrate, such as metals, carbon, conducting polymers, oxides, or carbides.…”
Section: Introductionmentioning
confidence: 99%
“…4 Fuel cell technology is considered to be one of the most promising, efficient, and sustainable zeroemission technologies available for electrochemical energy conversion devices. 5,6 However, some drawbacks have hampered the large-scale commercialization of fuel cells, including their susceptibility toward methanol and carbon monoxide (CO) deactivation, unsatisfactory long-term durability, and the high costs of platinum (Pt)-based electrocatalysts. 7,8 However, the biggest limitation of fuel cells by far is the sluggish kinetics of the cathodic oxygen reduction reaction (ORR), which is the major limiting half-reaction that hinders the further progress of this technology.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of experimental and theoretical researches have demonstrated that heteroatom (such as N, B, P, and S)-doped carbon revealed excellent electrocatalytic ORR performance with superior stability. [12][13][14][15][16] The origin of activity is mainly attributed to the replacement of some carbon atoms in the sp 2 lattice of graphitic carbon by heteroatoms. Then, the changed electronic arrangement of carbon-based materials tailors their electron donor properties, which are responsible for the abundant favorable active sites for electrochemical reactions.…”
Section: Introductionmentioning
confidence: 99%